The extracellular matrix protein fibronectin promotes metanephric kidney development - Skoczynski, Kathrin; Kraus, Andre; Daniel, Christoph; Büttner-Herold, Maike; Amann, Kerstin Ute; Schiffer, Mario; Hermann, Kristina; Herrnberger-Eimer, Leonie; Tamm, Ernst R.; Buchholz, Björn (Pflügers Archiv: European Journal of Physiology, 2024)
Complex interactions of the branching ureteric bud (UB) and surrounding mesenchymal cells during metanephric kidney development determine the final number of nephrons. Impaired nephron endowment predisposes to arterial hypertension and chronic kidney disease. In the kidney, extracellular matrix (ECM) proteins are usually regarded as acellular scaffolds or as the common histological end-point of chronic kidney diseases. Since only little is known about their physiological role in kidney development, we aimed for analyzing the expression and role of fibronectin. In mouse, fibronectin was expressed during all stages of kidney development with significant changes over time. At embryonic day (E) 12.5 and E13.5, fibronectin lined the UB epithelium, which became less pronounced at E16.5 and then switched to a glomerular expression in the postnatal and adult kidneys. Similar results were obtained in human kidneys. Deletion of fibronectin at E13.5 in cultured metanephric mouse kidneys resulted in reduced kidney sizes and impaired glomerulogenesis following reduced cell proliferation and branching of the UB epithelium. Fibronectin colocalized with alpha 8 integrin and fibronectin loss caused a reduction in alpha 8 integrin expression, release of glial-derived neurotrophic factor and expression of Wnt11, both of which are promoters of UB branching. In conclusion, the ECM protein fibronectin acts as a regulator of kidney development and is a determinant of the final nephron number.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Alpha 8 integrin; Branching; Fibronectin; Kidney development; Nephron number